2017
DOI: 10.3791/55455
|View full text |Cite
|
Sign up to set email alerts
|

Using Wavelet Entropy to Demonstrate how Mindfulness Practice Increases Coordination between Irregular Cerebral and Cardiac Activities

Abstract: In both the East and West, traditional teachings say that the mind and heart are somehow closely correlated, especially during spiritual practice. One difficulty in proving this objectively is that the natures of brain and heart activities are quite different. In this paper, we propose a methodology that uses wavelet entropy to measure the chaotic levels of both electroencephalogram (EEG) and electrocardiogram (ECG) data and show how this may be used to explore the potential coordination between the mind and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…Its inverse correlation with the spectral power in the low frequencies led the authors to hypothesize that a meditation feature would be its lower complexity because practitioners engage in less distraction during the practice. Gao et al ( 2016 ), Sik et al ( 2017 ) also reported decrease in complexity related to CDM meditation. They combined both the Wavelets Transform with the complexity and source analysis, to analyze the MBSR program.…”
Section: Non-linear Techniquesmentioning
confidence: 91%
See 1 more Smart Citation
“…Its inverse correlation with the spectral power in the low frequencies led the authors to hypothesize that a meditation feature would be its lower complexity because practitioners engage in less distraction during the practice. Gao et al ( 2016 ), Sik et al ( 2017 ) also reported decrease in complexity related to CDM meditation. They combined both the Wavelets Transform with the complexity and source analysis, to analyze the MBSR program.…”
Section: Non-linear Techniquesmentioning
confidence: 91%
“…In the meditation field, multimodal approaches are seen since the first studies appearing in the 70's, which aimed at incorporating complementary information from peripheral physiology, like skin resistance, heart rate and respiration (Wallace, 1970 ; Wallace et al, 1971 ; Elson et al, 1977 ; Fenwick et al, 1977 ; Hebert and Lehmann, 1977 ; Corby et al, 1978 ). Recently, new analyses have combined these signals (Gao et al, 2016 ; Chandra et al, 2017 ; Sik et al, 2017 ; Jiang et al, 2020 ).…”
Section: Multimodal Studiesmentioning
confidence: 99%
“…However, the explanatory power of an interaction analysis via correlation of different analysis parameters based even on different biosignals, as conducted in John et al (2020), has to be handled with caution. Investigating an interaction between brain and heart activity proves problematic due to various signal content between the (neuro-)physiological systems (Sik et al, 2017). Furthermore, different data preprocessing, e.g., bandpass and artifact filtering, as well as calculation techniques, e.g., time-versus frequency domain, dependent on the respective brain or heart measure aggravates besides varying value ranges of these parameters an interference-free interaction analysis.…”
Section: Introductionmentioning
confidence: 99%
“…The most popular approaches for analyzing nonlinear signal characteristics investigate signal irregularity based on the entropy theory (Shannon, 1948). Commonly, irregularity of the EEG is characterized as signal noise, whereas it may contain valuable information (Sik et al, 2017) and seems relevant for a healthy, efficient and flexible neural function (Kosciessa et al, 2020). Regarding ECG, it is well known that the heart activity (HRV) needs to contain some noise or irregularity for being healthy (Peng et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation